INNOVATION TECHNOLOGIES FOR PROVIDING MEDICAL SERVICES (INNOVATIVE ECONOMY, 2022)
Zhukovska A.Yu., Chyhur O.V. INNOVATION TECHNOLOGIES FOR PROVIDING MEDICAL SERVICESPurpose. The aim of the article is to study the global and domestic market of telemedicine services and substantiate the need to stimulate its development.Methodology of research. The theoretical and methodological basis of the research is the fundamental provisions of modern economic theory, scientific works of leading foreign and domestic scientists, international and domestic normative legal acts on health care issues. General scientific and special research methods were used to achieve the goal, in particular: the system analysis method – for the study of the telemedicine market as a system; method of structural analysis – for the analysis of global and domestic telemedicine markets; comparison method – to compare global and domestic trends in the development of the telemedicine market.Findings. In the article: the state and prospects for the development of the global telemedicine market are investigated; the structure of the global telemedicine market is analysed by types of services, by types of assistance, by specialization and by form of communication; the main models of interaction between telemedicine subjects developed by foreign practice are investigated; it was established that the domestic market of telemedicine is still at the stage of formation; the institutional support for the operation of the telemedicine market is analysed and its shortcomings are identified; four main segments of the domestic telemedicine market are singled out; it was established that the most capacious segment of the telemedicine market in Ukraine is telemedical consultation; the factors that stimulate and restrain the development of the telemedicine market in Ukraine are identified; measures to stimulate the development of the telemedicine market, which should be implemented by state authorities, health care institutions, and IT companies, are proposed.Originality. The article substantiates the prospects for the development of the domestic telemedicine market and proposes measures to stimulate it.Practical value. The measures proposed in the article to stimulate the development of the telemedicine market in Ukraine are of practical importance and can be used in the development of strategic guidelines for the development of the health care system.Key words: health care, e-medicine, telemedicine, teleconsultation, innovative technologies.
Keywords: health care; e-medicine; telemedicine; teleconsultation; innovative technologies